The roles of the talent development environment on athlete burnout : a qualitative study - Li, C.; Wang, C. K. J.; Pyun, D. Y. (International Journal of Sport Psychology, 2017)
Grounded on basic psychological needs theory (Deci & Ryan, 2000), this qualitative study investigated the impacts of the talent development environmental factors on athlete burnout. Talented youth athletes with high and low burnout levels (n = 38; each group had 19 participants) were recruited to attend focus-group interviews. Thematic analysis led to five environmental themes: long-term development focus, holistic quality preparation, support network, communication, and alignment of expectations. Athletes with high burnout levels were likely to experience more detrimental and less conducive talent development environmental antecedents compared to those who were with low burnout levels. It was concluded that the talent development environmental factors are important antecedents for burnout prevention.